Design of an Artificial Glycosidase - Metallopeptides that Remove H-Antigen from Human Erythrocytes - Yu, Zhen (Angew Chem Int Ed Engl, 2017)
Catalysts that promote carbohydrate degradation are of wide potential application, but the use of either enzyme glycosidases or small-molecule catalysts in biological systems raises significant challenges. Herein we demonstrate a novel strategy for the design of synthetic agents that mimic natural glycosidases and address current problems for biological use. The strategy is illustrated by application to the development of potential blood substitutes for rare Bombay blood that is characterized by a deficiency of H-antigen. Metallopeptides with 16 to 20 amino acids have been constructed as artificial fucosidases that exhibit selective carbohydrate cleavage reactivity toward L-fucose rather than D-glucose. Selective fucose cleavage from the H-antigen saccharide promotes efficient removal of H-antigen on erythrocytes and fulfils the conversion of regular human O-type erythrocytes to potential blood substitutes for rare Bombay blood.